THE AFFORDANCES OF TECHNOLOGY IN BUILDING THE ASEAN COMMUNITY THROUGH GRADUATE EDUCATION - Saludadez, Jean A (LPPM Universitas Terbuka, 2018)
This paper highlights the affordances of technology in building the ASEAN community through graduate education. Specifically, the paper shall focus on the development and the delivery of the ASEAN Studies Graduate Program being offered online by the University of the Philippines Open University (UPOU). The program hopes to develop graduates who can contribute to an enhanced and heightened ASEAN community’s consciousness and awareness of its ties of history, culture and bound by a common regional identity but celebrating diversity. The paper shall share the development of the program structure and of the course materials that was accomplished through the collaboration of five open universities in the ASEAN region bound by a philosophy that the commonly shared ASEAN aspiration and dynamics could only be well understood by the ASEAN peoples themselves through a system of knowledge and body of research and repository of data and information on the region in its individual member nations and in its collective character as a regional entity. Further the paper shall share the delivery of the program that is framed by the Open and Distance eLearning or ODeL philosophy characterized by openness, inclusion, resource sharing, access and equity of open learning and learner-centeredness, flexibility, active learning, interactivity, ubiquity, connectivity and constructivism view of e-learning. The paper shall conclude with the challenges of a graduate program within an ODeL framework.